2022
DOI: 10.1001/jamanetworkopen.2022.11321
|View full text |Cite
|
Sign up to set email alerts
|

Use of Novel Strategies to Develop Guidelines for Management of Pyogenic Osteomyelitis in Adults

Abstract: IMPORTANCE Traditional approaches to practice guidelines frequently result in dissociation between strength of recommendation and quality of evidence. OBJECTIVE To construct a clinical guideline for pyogenic osteomyelitis management, with a new standard of evidence to resolve the gap between strength of recommendation and quality of evidence, through the use of a novel open access approach utilizing social media tools.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 75 publications
0
19
0
Order By: Relevance
“…This meta-analysis compiled all anatomic sites of osteomyelitis; moreover, it was published in 2013, so it did not include some studies we included in our systematic review. A more recent meta-analysis comprising 1321 patients concluded that the overall treatment success was not significantly different between oral step-down therapy and IV-only antibiotic therapy for the treatment of bone infections (Wald-Dickler et al, 2022). However, in the studies included in this meta-analysis, VO was either excluded (Mader, 1990;Gomis, 1999;Euba et al, 2009), or the number of patients with this specific bone infection was too low to draw a significant conclusion (Li et al, 2019).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…This meta-analysis compiled all anatomic sites of osteomyelitis; moreover, it was published in 2013, so it did not include some studies we included in our systematic review. A more recent meta-analysis comprising 1321 patients concluded that the overall treatment success was not significantly different between oral step-down therapy and IV-only antibiotic therapy for the treatment of bone infections (Wald-Dickler et al, 2022). However, in the studies included in this meta-analysis, VO was either excluded (Mader, 1990;Gomis, 1999;Euba et al, 2009), or the number of patients with this specific bone infection was too low to draw a significant conclusion (Li et al, 2019).…”
Section: Discussionmentioning
confidence: 93%
“…Some patients with bacterial NVO can reasonably benefit from parenteral therapy at the beginning given the clinical instability, concomitant bacteremia or endocarditis, and difficulty absorbing oral medication. Thus, in this hypothetical trial, we propose to randomize the patients to switch to oral or prolonged parenteral therapy when recently published criteria are met: (a) clinical stability (hemodynamically and no spinal instability), (b) adequate source control, (c) likelihood to absorb oral medications, (d) an available oral regimen used in published studies to cover the pathogen, (e) no psychosocial reasons that preclude the safe use of oral therapy, and (f) any other concomitant infection which requires a prolonged course of intravenous antibiotic therapy (Spellberg et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have also recently summarized the literature on oral therapy for the treatment of osteomyelitis, bacteremia, and endocarditis [ 30 , 101 , 102 ]. The overwhelming concordance of data have demonstrated that oral therapy is effective for these infections, contrary to fixed, firm beliefs otherwise.…”
Section: Modern Data For Shorter Is Better and Oral Therapymentioning
confidence: 99%
“…The overwhelming concordance of data have demonstrated that oral therapy is effective for these infections, contrary to fixed, firm beliefs otherwise. There are more than 40 published observational studies demonstrating that oral therapy is effective for osteomyelitis [ 26 , 102 ] and more than 15 such studies demonstrating efficacy for endocarditis [ 30 ]. More importantly, there are 21 randomized controlled trials demonstrating that oral therapy is at least as effective as IV-only therapy for these diseases, including 9 trials of osteomyelitis, 10 trials of bacteremia, and 3 trials of endocarditis (1 trial included separate cohorts of osteomyelitis and bacteremia) ( Table 2 ) [ 101 , 103 ].…”
Section: Modern Data For Shorter Is Better and Oral Therapymentioning
confidence: 99%